Effects of resin content on mechanical and physical properties of treated kenaf particleboard / Nur Liyana Aifa Mahammad Asri ... [et al.] - Mahammad Asri, Nur Liyana Aifa; Mohamed Anwar, Ainil Idzaty; Najib, Nur Atiqah; Gisip, Judith (UiTM Press for the Research Management Center (IRMI), Universiti Teknologi MARA, 2022)
Kenaf whole stems were obtained from kenaf plantation located in Chendor, Cherating, Pahang. The stems were cut into small particles with sizes ranging between 0.5 mm to 2.0 mm. Kenaf particles were treated using 2 % NaOH solution. Phenol formaldehyde (PF) adhesive was used to bind the kenaf particles together with resin contents of 8 and 10 %. The objectives of this study were to evaluate the effect of resin content on mechanical and physical properties of treated kenaf particleboard. The boards were cut and tested according to the Malaysian Standard (MS1787:2004) for furniture grade particleboards for use in humid condition. Results showed that the values of modulus of rupture, modulus of elasticity and internal bonding strength increased with an increase in resin content, while thickness swelling and water absorption increased with a decrease in resin content. Kenaf board treated with sodium hydroxide gave the highest value of bending strength and internal bonding strength compared to untreated particleboard which acted as a control board. Although all boards did not achieve the minimum standard values requirement according to the Malaysian standard, kenaf has been proven to have a great potential as raw materials in the particleboard industry. Further studies are needed to improve its properties particularly for exterior applications.